EFEKTIVITAS MEDIA PEMBELAJARAN ARTICULATE STORYLINE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - Indri Anugrah Ramadhani; Harnianti Harnianti; Firman Firman (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Learning network system administration, most students are less enthusiastic and focused on learning and their learning achievements are also still many below the Minimum Completeness Criteria (KKM), this is evidenced from 18 class X TKJ students only 10%, who passed this subject, factor what affects this is that they are lacking in terms of understanding the material if it is only conveyed through explanations using modules or e-modules that are less interesting. This research aims to improve student learning on class X TKJ network operating system material at Muhammadiyah Aimas Vocational School. The type of research used is MDLC (Multimedia Development Life Cycle). The results of the trial assessment of several aspects of the media program 96.6% received a very good category, the instrument rating aspect with a percentage of 100% was in a very good category, and for material aspects it received a percentage of 94.6% which also received a very good category, the last one was a response assessment students to the media and get a percentage of 79% with a very good category. the results of the media effectiveness test from the pretest test with an average of 32.00 and the posttest test with an average of 80.28, indicate an increase in student achievement performance in the class X TKJ Network Operation System material at SMK Muhammadiyah Aimas.